(untitled) (Biological Sciences - PJSIR, 2005)
Low-grade chromite of Muslim Bagh, Balochistan, Pakisktan was beneficiated to produce chromite concen- trate by cationic flotation using disodium n-octadecyl sulfosuccinamate as collector. Effect of various parameters such as grind size, pulp density, pH, and conditioning time on the overall grade and recovery of chromite was also investigated. Particle liberation studies during this investigation revealed that grinding of the ore upto -80 # liberated over 89% of chro- mite. However, presence of excessive amounts of fines inhibited the flotation. The ore, initially containing 38% Cr2O3, was upgraded to concentrates assaying Cr2O3 upto 60% with an overall Cr2O3 recovery of 82%.